FEMS microbiology reviews (Oxford Univ. Press, 1985)
The earlier volumes of FEMS Microbiology Reviews (FEMSRE) is published with a volume number in the sequence of FEMS Microbiology Letters volume numbers published in that year. Therefore these early volumes can be found in the back files of FEMS Microbiology Letters. Since 1993 it is published as a separate journal
Gesehen am 01. Februar 2017
Keywords: Zeitschrift; Online-Ressource; Mikrobiologie